Synthesis of 5H-Chromeno[4,3-b]pyridin-5-one derivatives as a backbone of natural product polyneomarline C scaffolds in presence of Et3N and NH4OAc in EtOH - Shrishnu Kumar Kundu; Susanta Patra; Chayan Sardar; Sunil Kumar Bhanja; Prasanta Patra (Chimica Techno Acta)
A green one-pot synthesis of 5H-Chromeno[4,3-b]pyridin-5-one derivatives which are the main core of the natural product of Polyneomarline C is described by the reaction of 4-chloro-3-formyl coumarin and different cyclic and acyclic compounds having active methylene group in presence of Et3N and NH4OAc in EtOH. The advantages of this strategy are good yields, no need for the chromatographic separation and the absence of heavy metal catalysts and toxic by-products. The 4-chloro-3-formyl coumarin is obtained by Vilsmeier Heck reaction of 4-hydroxy coumarin.